PEMBERDAYAAN KELOMPOK ISTRI NELAYAN DESA MOTTO MELALUI DIVERSIFIKASI PRODUK OLAHAN STIK CUMI - Fitroh Dwi Hariyoto; Agusta Putri Balqis Linda Soeharso; Daniel Heintje Ndahawali; Itje Danti Wewengkang; Fidel James Bonifacio Ticoalu (Universitas Mataram, 2023)
Bitung City is the center of fishery resources in Indonesia, including squid. One of Bitung City's squid producers is Motto Village, which utilizes squid catches directly or processed into squid stick products by a group of fishermen's wives. The fishermen's wives group consists of fishermen's wives with a side business of processing squid catches. The making of squid sticks is based on the traditional recipe of Motto Village and has not been standardized. The production and marketing activities are not yet optimal so it is necessary to carry out empowerment activities to increase production with the ultimate goal is increasing income and a better standard of living. This activity was carried out in September 2021 using the method of counseling and training on how to make good squid stick products (GMP). The activity process includes providing information and practice of making squid stick preparations as well as marketing methods and designs generally adapted to current market conditions. This empowerment activity results in the fishermen's wives group knowing how to produce good squid sticks well and can understand the promotion and marketing steps. Squid has good nutritional content so proper processing is needed to reduce the nutritional content. The marketing model is done by utilizing existing facilities and technology, such as using social media. Promotion on social media has proven to get more results relatively easily. For this reason, the concept of brand identity must be optimized so that squid stick products can be known more widely and stick in the minds of buyers. Through this empowerment, the fishermen's wives group better understands how to improve product quality while developing the market through product packaging design.